2008
DOI: 10.1161/circulationaha.107.758623
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Opposing Roles of Extracellular Signal-Regulated Kinase 1/2 and p38 Mitogen-Activated Protein Kinase in the Regulation of Cardiac Contractility

Abstract: Background-Extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 mitogen-activated protein kinase (p38-MAPK) have been shown to regulate various cellular processes, including cell growth, proliferation, and apoptosis in the heart. However, the function of these signaling pathways in the control of cardiac contractility is unclear. Here, we characterized the contribution of ERK1/2 and p38-MAPK to the inotropic effect of endothelin-1 (ET-1). Methods and Results-In isolated perfused rat hearts, infusion of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 49 publications
(60 reference statements)
5
59
0
10
Order By: Relevance
“…We found that stretch-induced increase in cardiac contractility in isolated rat atria was enhanced by inhibition of p38 MAPK. There is already convincing data indicating a negative role for the p38 MAPK mediating the inotropic effect in ventricular cardiomyocytes both in vivo and in vitro (27,28,44) (for review, see Ref. 22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that stretch-induced increase in cardiac contractility in isolated rat atria was enhanced by inhibition of p38 MAPK. There is already convincing data indicating a negative role for the p38 MAPK mediating the inotropic effect in ventricular cardiomyocytes both in vivo and in vitro (27,28,44) (for review, see Ref. 22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AF is also associated with increased atrial mRNA levels of endothelin-1 (ET-1) (31). In the left ventricle, ET-1 augments left ventricular contractile function and activates hypertrophic signaling pathways (43,44). In fact, the signaling mechanisms regulating hypertrophic response in ventricular cardiomyocytes have been studied extensively, but signaling mechanisms involved in stress response in atrial myocardium are not well understood.…”
mentioning
confidence: 99%
“…Mechanizmusát tekintve, a β-AR-választól eltérően, az ET-1 elsősorban a miofi lamentumok Ca 2+ -érzékenységét fokozva képes növelni a szívizom-össze-húzódások erejét. A peptid inotrop hatását az ET A -receptorok közvetítik az epidermalis növekedési faktor receptor (EGFR) extracelluláris szignál által regulált kináz 1/2 (ERK1/2)−p90 riboszomális S6-kináz−Na + / H + cseremechanizmus jelátviteli út aktivációja révén [17].…”
Section: Az Et-1 Szívserkentő Hatása éS Az Endogén Ros-termelődésunclassified
“…Eredményeink szerint az ERK1/2 aktivációja, amely alapvető szerepet tölt be az ET-1 pozitív inotrop hatásá-nak közvetítésében [17], döntően ROS-érzékeny, mivel az N-acetil-cisztein és az apocynin is szignifi kánsan csök-kentette az ET-1 indukálta ERK1/2-foszforilációt [14]. Korábban kimutattuk, hogy az ET-1 az EGFR transzaktiváció révén váltja ki az ERK1/2 aktivációját [17].…”
Section: Az Et-1 Szívserkentő Hatása éS Az Endogén Ros-termelődésunclassified
See 1 more Smart Citation